1998
DOI: 10.1002/(sici)1097-0134(19980201)30:2<155::aid-prot5>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures and properties of de novo circularly permuted 1,3-1,4-β-glucanases

Abstract: The 1,3-1,4-beta-glucanases from Bacillus macerans and Bacillus licheniformis, as well as related hybrid enzymes, are stable proteins comprised of one compact jellyroll domain. Their structures are studied in an effort to reveal the degree of redundancy to which the three-dimensional structure of protein domains is encoded by the amino acid sequence. For the hybrid 1,3-1,4-beta-glucanase H(A16-M), it could be shown recently that a circular permutation of the sequence giving rise to the variant cpA16M-59 is com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…Several earlier crystallographic studies of laboratory-permutated proteins have shown only minor deviations in those proteins’ tertiary structures except in two regions: the original termini and the newly created N and C-termini 2832. The fusion of the original termini often creates structurally poorly defined loops, in particular in the presence of extra amino acids to link distant residues.…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier crystallographic studies of laboratory-permutated proteins have shown only minor deviations in those proteins’ tertiary structures except in two regions: the original termini and the newly created N and C-termini 2832. The fusion of the original termini often creates structurally poorly defined loops, in particular in the presence of extra amino acids to link distant residues.…”
Section: Introductionmentioning
confidence: 99%
“…Several other monomeric proteins have since been circularly permuted through genetic manipulations, all of which maintain a nativelike function. [3][4][5][6][7][8][9][10][11] Single subunits of multimeric proteins can also withstand circularly permuted sequences. For example, circularly permuted catalytic chains of aspartate transcarbamoylase combined in vitro with regulatory chains produced a folded and functional multimeric protein.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increased activities of the circular enzyme variants LicA-C1, LicA-C2, and LicA-C5 compared to the linear LicA-L1 suggest that the introduced junction and loop do not result in activity loss of the enzyme. Earlier studies have shown that circular permutations in the compact jelly roll domain of LicA are tolerated and did not result in significant changes in the enzymatic activity or tertiary structure [37, 38]. Therein, it was shown that the direct peptide bond linking of the N- and C-termini, without the addition of extra residues, did not introduce strain into the molecule.…”
Section: Resultsmentioning
confidence: 99%